UHF RFID Read Range Control Based on Visual Basic.NET for Automation Tool’s Crib - Aldo Rahmad Ageng; Ari Santoso; Imam Arifin; Ayyasy Azzurqi; Moh. Abdul Hady (IPTEK Journal of Proceedings Series, 2019)
Asset maintenance is a preventive action from tool’s damage. Place for production tool’s usually called by tool’s crib, is a facility for field engineer on the production line. Generally, tool’s maintaining system that operate in industry checked and maintain in every month. Nevertheless, administration check and maintenance are unbalanced that delayed transactional and identification process. Automating tool’s crib applied to change transaction and administration activity on the system become automatic using RFID (Radio Frequency Identification) and database on Automation Tool’s Crib project. Used RFID on this project have a read range that far too wide on the identification process. So, controlling read range of a RFID on Automation tool’s Crib to reduce error on transaction and identification process. Controlling RFID based on Visual Basic.NET are able to reduce error of scanning process on Automation Tool’s Crib from 7.5% to 1.2%.